(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides a review of the literature on the results of studies to identify etiopathogenetic factors, clinical course, features of diagnosis and treatment of glomerulonephritis in children. According to extensive literature, viral infections are temporarily associated with the onset of many glomerular diseases, especially in children. In other cases of glomerulonephritis, where the infection is clinically asymptomatic, viral syndromes may still be implicated as a trigger. However, convincing evidence for the viral etiology of most glomerular diseases is still lacking.